(untitled) (Philological Studies, 2019)
The globally ruling techno-scientific-economic-political complex has been equally and similarly endangering both "first nature" (i.e. bios and physis) and "second nature" (i.e. human culture in the widest sense). An integrative approach to the key problems of today’s world requires that, in terms of their subject, we regard these two fields jointly while appreciating their heterogeneity. Methodologically speaking, it requires that we develop pluriperspectivism. Bioethics and multiculturalism meet at both levels. Accordingly, following an analysis of the techno-scientific-economicpolitical matrix, this paper discusses the interrelations between bioethics and multiculturalism so as to show that only an integrative and pluriperspectival approach enables us to detect, articulate and solve the problems that issue from the radical endangerment of both nature and culture. Special attention is given to some of Vandan Shiva’s works, which are useful for recognising the nature and global dimensions of the said problems, as well as the Lošinj Declaration of Biotic Sovereignty (2004), which represents a solid conceptual basis for the protection of "biocultural sovereignty" and "biocultural rights".